Learning and intergenerational communication through digital storytelling in the first grades of primary school: Yesteryear Jobs - Mouchtari Efthalia; Meimaris Michalis; Gouscos Dimitris; Sfyroera Maria (Cultural Science)
The research reported in this paper examines how two different groups, primary schoolchildren and elderly people, could close the generation gap through a digital storytelling-based interaction framework that can result in learning for the younger and intergenerational communication. Yesteryear jobs have been chosen as the theme of this research, based on the premise that, as computers and automated systems increasingly take the jobs humans once held, entire professions become extinct, and some of these endangered professions, from a milkman to an iceman, could become better known to primary school children through storytelling from elderly people. In this respect, the research reported in this paper has combined digital storytelling with techniques as traditional as theatrical games, in order to create a blended framework for intergenerational interactions. The research project was realized in the 15th Primary School of Piraeus, in Athens, Greece during academic years 2011-12 and 2012-13. It has involved a 6-month empirical study and embraced skills such as literature reading, story and song listening, painting, creating digital stories as well as improvising through theatrical games. The evaluation tools for the outcomes of this project comprised a questionnaire, participant observation, informal interviews and a video rubric for evaluating the digital creations of schoolchildren.